Report on Economies in Construction Costs - Planning Commission (Planning Commission, Government of India, 1968)
The report presents a comprehensive framework for achieving economies in construction costs while improving efficiency, quality, and sustainability in the construction industry in India. It highlights the critical role of effective pre-planning, emphasizing that significant cost savings can be realized when projects undergo thorough analysis, proper design development, and structured planning before the commencement of construction activities. The document advocates the adoption of modern construction techniques, advanced design principles, and updated technological practices to enhance productivity and reduce unnecessary expenditures. Since building materials constitute a major share of total construction costs, the report stresses the need for better production, assessment, and supply management of materials, along with the promotion of alternative materials such as lightweight aggregates, slag-based cement, and cellular concrete. It also underscores the importance of standardization through uniform construction codes, standardized schedules of rates, and the widespread adoption of national guidelines to maintain consistency across states. Strong quality control systems, including field laboratories and systematic inspection methods, are recommended to ensure adherence to standards and durability of structures. Institutional support mechanisms such as the establishment of a Construction Finance Corporation and improved access to financial resources for contractors are proposed to facilitate modernization and encourage industry participation. Additionally, the report calls for improved logistics, mechanization in quarrying and material production, and the creation of equipment pools to enhance the utilization of construction machinery. Organizational reforms, including the establishment of a centralized authority and the strengthening of institutions responsible for construction oversight, are suggested to improve coordination and resource allocation. Emphasis is also placed on training and skill development for engineers, architects, and craftsmen to ensure the adoption of modern practices and maintain high professional standards. Overall, the report proposes a multifaceted strategy combining technological advancement, financial support, material management, administrative reform, and human resource development to strengthen the construction sector and enable the efficient execution of national development programs.
Planning Commission (Construction Division) New Delhi
Keywords: Construction Cost Optimization; Pre-Planning in Construction; Modern Construction Techniques; Material Cost Control; Quality Control Mechanisms; Construction Finance Corporation; Standardization of Building Practices; National Building Code; Construction Equipment Utilization; Training and Skill Development; Alternative Construction Materials; Administrative and Organizational Reforms